Forage research in India - the post-Independence scenario - MAL, BHAG (The Indian Journal of Agricultural Sciences, 2013)
The present status of research on forage crops and related aspects is fairly satisfactory, though some major challenges'still exist. Forage production has shown a tremendous change since the Independence, as 121 recognized varieties offorage crops suitable for different regions of country and their package of practices are available. The forage cultivationand its resultant returns increased manifold owing to an easy access offarmer to the research findings and technologies,which is clear from the fact that India recorded the highest milk production in world during 1996-97. The productivityof cultivated forage crops increased by more than 2 times (250 tonnes/ha) from an average of 100 tonnes green forage/ha during sixties because of adoption of technologies generated through research inputs in field of forage production.The biomass production from degraded land also showed a great increase of 3.5 tonnes/ha from 1 tonne/ha duringsixties. Adoption of watershed technologies developed at the Indian Grassland and Fodder Research Institute, Jhansi,increased the productivity of wastelands by 7-8 times, resulting in income offarmers from Rs 1 968/year/family to Rs 29 400/year/family. Major constraints and future thrust areas are also given in this article.